2021
DOI: 10.1177/00420980211033085
|View full text |Cite
|
Sign up to set email alerts
|

Social capital and perceived tenure security of informal housing: Evidence from Beijing, China

Abstract: Perceived tenure security is recognised to affect the socioeconomic behaviours and wellbeing of informal settlement dwellers. The provision of perceived tenure security is centred on the developmental agenda as a key policy alternative of tenure legalisation. Despite the consensus about its importance, the reason perceived tenure security is different amongst dwellers remains unclear. To fill this gap, we introduce social capital theory to understand the formation of and disparity in perceived tenure security.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 77 publications
0
2
0
Order By: Relevance
“…The first challenge recognised by local governments is the informality of the PRS. Different from most past literature that regards urban village housing as informal while commercial housing as formal (Wang, et al, 2009;Zhang, 2021), informality here means that tenancies are 'hidden from the purview of the State', thus making 'regulation and recourse difficult to enforce' (Parkinson, et al, 2022).…”
Section: Challenges As Perceived By the Local Governmentsmentioning
confidence: 92%
“…The first challenge recognised by local governments is the informality of the PRS. Different from most past literature that regards urban village housing as informal while commercial housing as formal (Wang, et al, 2009;Zhang, 2021), informality here means that tenancies are 'hidden from the purview of the State', thus making 'regulation and recourse difficult to enforce' (Parkinson, et al, 2022).…”
Section: Challenges As Perceived By the Local Governmentsmentioning
confidence: 92%
“…Informal approaches are preferred and applied in dispute resolution more often than formal approaches [22]. Research on social capital has already revealed its important role in protecting private property [23,24] and preventing deviant behaviours in water use [25]. When households themselves exist in a context of weak tenure and governance, it has been found that that are more active in tenure protection, for example by building salient boundaries, allocating defensive labour and planting trees to declare secure claims and prevent possible violations and disputes [26][27][28].…”
Section: Introductionmentioning
confidence: 99%